2014
DOI: 10.1002/elps.201400077
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation of 12 cathinone analogs by cyclodextrin‐assisted capillary electrophoresis with UV and mass spectrometry detection

Abstract: In this study, a rapid chiral separation of 12 cathinones analogs has been developed and validated using cyclodextrin-assisted CE with UV and TOF-MS detection. Optimum separation was obtained on a 57.5 cm × 50 μm capillary using a buffer system consisting of 10 mM β-cyclodextrin (β-CD) in a 100 mM phosphate buffer for CE-UV, and 0.6% v/v highly sulfated-γ-cyclodextrin (HS-γ-CD) in a 50 mM phosphate buffer for CE-MS. In the CE-MS experiment, a partial filling technique was employed to ensure that a minimum amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 48 publications
1
87
0
Order By: Relevance
“…[31][32][33][34] Since the substance is available as hydrochloride, the polar organic mode arrangement with ethanol as the bulk mobile phase was assumed to provide the best results. [31][32][33][34] Since the substance is available as hydrochloride, the polar organic mode arrangement with ethanol as the bulk mobile phase was assumed to provide the best results.…”
Section: Enantioseparation Of Butylonementioning
confidence: 99%
“…[31][32][33][34] Since the substance is available as hydrochloride, the polar organic mode arrangement with ethanol as the bulk mobile phase was assumed to provide the best results. [31][32][33][34] Since the substance is available as hydrochloride, the polar organic mode arrangement with ethanol as the bulk mobile phase was assumed to provide the best results.…”
Section: Enantioseparation Of Butylonementioning
confidence: 99%
“…In the study, it was observed that for chiral separation of a range of synthetic cathinones (2-, 3-, 4-regioisomers of methylmethcathinone, methylethcathinone and ethylethcathinone), these two β-CDs were found to be complementary on their chiral selectivities. Interestingly, another two CDs highly sulfated-γ-CD (HS-γ-CD) and native β-CD were also found to give complementary chiral separation for some synthetic cathinones [23]. Native β-CD did not separate 4-methoxymethcathinone and 4-fluoromethcathinone enantiomers but these were separated using HS-γ-CD, while HS-γ-CD did not separate N,N-dimethylcathinone, ethcathinone, pentedrone, and buphedrone enantiomers but these were separated by native β-CD.…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 99%
“…Merola et al used beta-CD and HS-gamma-CD for achieving the chiral separation of 12 cathinone analogs, belonging to the benzoylethanamine class and sold illegally as "bath salts," by means of PF-CZE-ESI-TOF MS [79]. These compounds differ from one another by the presence of substituents that may include halogen, dioxol, and alkyl groups; hence, a highly efficient and selective method for the discrimination of such closely related compounds is needed.…”
Section: Drugs Of Abusementioning
confidence: 99%